Klassmärken – tecken som röjer: Om motstridiga logiker i ett institutionaliserat möte - Lilja, Agneta (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2023)
My late grandmother (b. 1904) considered tattooes and whiskers to be class markers revealing a simple background; criminals and sailors had tatooes and footmen wore side-whiskers. My father thought talking too loud and chewing bubble gum were social class markers. According to my recently conducted interviews, bad teeth and crocs are todays class markers, as are certain names, such as Benny, Conny and Sonny. The youngest interviewees made a significant difference between the working class and so called white trash. They also mentioned ”Ullared”, a reality soap opera showing people with over-explicit examples of white trash class markers.